2007
DOI: 10.1016/j.jtcvs.2006.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-based infrared light scanner as a tool to assess conduit quality in coronary artery bypass surgery

Abstract: OCT imaging provides an accurate, real-time, and reproducible means for assessing saphenous vein graft and radial artery graft bypass conduits. As a quality assurance tool, this technology might afford a more objective basis for conduit selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…Four separate 5 thick sections were cut from each graft. Intimal and media thickness was measured in hematoxylin and eosin stained sections using image analysis software (Bioquant Nova Prime, Nashville, TN) and the intima-media ratio was calculated for each graft [13].…”
Section: Preexisting Intimal Thickeningmentioning
confidence: 99%
“…Four separate 5 thick sections were cut from each graft. Intimal and media thickness was measured in hematoxylin and eosin stained sections using image analysis software (Bioquant Nova Prime, Nashville, TN) and the intima-media ratio was calculated for each graft [13].…”
Section: Preexisting Intimal Thickeningmentioning
confidence: 99%
“…The change in mean luminal volume measured from the in situ and ex vivo OCT scans, a measure of RA spasm, was compared between groups using a t test. In preliminary data using discarded RA segments, we found that ERAH was associated with a fivefold increase in minor intimal injury vs open RA harvest [10]. Therefore, 25 RAs per group were expected to provide an 80% power to detect a fourfold difference in intimal injury between groups at p = 0.05.…”
Section: Statisticsmentioning
confidence: 90%
“…The OCT images were analyzed by 2 technicians blinded to group assignment, with harvesting injury categorized as minor when intimal disruption was restricted to the ostia of branch points and severe when the luminal surface was involved [10]. Luminal volume of the RA was calculated from OCT data using automated imaging processing software.…”
Section: Optical Coherence Tomography Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The radial scanner was developed for coronary artery characterisation [87]. The probe produces cross-sectional images of the vessel wall while it rotates (see Fig.…”
Section: Article In Pressmentioning
confidence: 99%